(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Background Low back pain is often associated with imbalances in hip muscle length and strength. It can result from prolonged over stretching of the innervated soft tissues when poor sitting or standing postures are maintained. These changes in muscular tone create muscle imbalance, which leads to movement dysfunction.Objective To evaluate the effect of stretching and strengthening exercises (Janda’s approach) with conventional treatment in the subjects with postural low back pain in terms of pain intensity, level of function, index of lumbar lordosis, muscle strength and muscle length.Method The study design was a single observer blinded randomized controlled trial. 200 subject aged between 18 to 55 years, clinically diagnosed with ergonomical low back pain with LCS were included. The subjects were randomly allocated to two groups. Group A (control group) was provided with moist pack and core stability exercises and Group B (experimental group) was given moist pack and core stability exercises along with stretching of illiopsoas, rectus femoris and erector spinae and strengthening of abdominal and gluteal muscle for 10 sessions.